X - LEARNING Y SU CONTRIBUCION EN EL PROCESO EDUCATIVO DE LOS ESTUDIANTES DE BÀSICA SUPERIOR EN LA UNIDAD EDUCATIVA DOCTOR ANTONIO ANDRADE FAJARDO, PERIODO ACADEMICO OCTUBRE 2023 – - LEORO ZAMBRANO YOMIRA NICOL (2024)
X-learning is a very useful tool in the students' learning process and has been a key technique for teaching, where they use it as a means to acquire more knowledge. This study was carried out to evaluate the contribution that x-learning has on the students of the Doctor Antonio Andrade Fajardo Educational Unit, in itself, its objective is to provide students with a more flexible and personalized learning experience, adapted to their needs. and individual preferences. Thus, x-learning is important in the educational process because it provides students with flexibility, personalization, access to a wide variety of resources and learning opportunities, and encourages collaboration and participation. This educational modality adapts to the individual needs of students, allowing them to learn at their own pace and according to their own circumstances. Furthermore, by integrating various learning modalities, x-learning enriches the educational experience, promoting deeper, more meaningful and collaborative learning. In an increasingly digital and globalized world, x-learning becomes an invaluable tool to prepare students for the challenges and opportunities of the 21st century, facilitating their academic, professional and personal development.